2023
DOI: 10.1108/k-08-2022-1145
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perceived usefulness of recommender systems and information sources on purchase intention

Abstract: PurposeThe current study aims to empirically analyze the influence of different information sources, together with the persuasiveness of recommender systems (RSs) on the consumer’s purchase intention (PI). It also expands the research on RSs from the point of view of consumer behavior and psychology, considering perceived usefulness and relevance. In addition, it analyzes how different types of personalized recommendations, along with non-personalized ones, influence PI.Design/methodology/approachThe proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Hanaysha [31] suggests perceived usefulness of advertisements stands as a core factor in evaluation of advertisement's value by consumers. In the context of social media advertisements, Mecan & Sitar [27] in a study conducted in Romania reported perceived usefulness of social media advertisements exhibiting positive relationship with purchase intention. In another study conducted by Hanaysha [31] conducted in United Arab Emirates on perceived usefulness of social media advertisements of fast foods, perceived usefulness of ads was reported sharing significant positive relationship with purchase intention.…”
Section: Perceived Usefulness Of Social Media Advertisements and Purc...mentioning
confidence: 99%
See 2 more Smart Citations
“…Hanaysha [31] suggests perceived usefulness of advertisements stands as a core factor in evaluation of advertisement's value by consumers. In the context of social media advertisements, Mecan & Sitar [27] in a study conducted in Romania reported perceived usefulness of social media advertisements exhibiting positive relationship with purchase intention. In another study conducted by Hanaysha [31] conducted in United Arab Emirates on perceived usefulness of social media advertisements of fast foods, perceived usefulness of ads was reported sharing significant positive relationship with purchase intention.…”
Section: Perceived Usefulness Of Social Media Advertisements and Purc...mentioning
confidence: 99%
“…The overall value of social media advertisements is assessed by consumers differently [24]. Several scholars [26,24,27] have suggested the overall value of social media advertisements comprises of advertisement's perceived usefulness, advertisement's entertainment and advertisement's irritation. Some scholars e.g.…”
Section: Social Media Advertisements and Purchase Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…They provided insights into different techniques and approaches, to enhance the accuracy and effectiveness of recommendation systems in diverse domains. Mican and Sitar-Taut [28] examined how the perceived value of information sources and recommendation systems affected the buying propensity of consumers. An attention-based dynamic user modeling and deep collaborative filtering recommendation technique was proposed by Wang et al [29].…”
Section: Related Workmentioning
confidence: 99%
“…Perceived usefulness has a positive and significant effect on behavioral intention to use mobile banking (Paramita & Hidayat, 2023). Mican and Sitar-Taut (2023) stated that the influence of the perceived usefulness of personalized recommendations strongly affects purchase intention for online shoppers.…”
Section: Perceived Usefulnessmentioning
confidence: 99%